Carbon Emission Effect of the Dock-Less Bike-Sharing System in Beijing from the Perspective of Life Cycle Assessment - Ding, Qingjiang; Li, Jinghui; Wang, Qixuan; Li, Chunhui; Yue, Wencong (Journal of Environmental Accounting and Management, 2026)
As the government has begun to promote the sharing economy and green travel, shared bikes have wide spread in many cities in China. Bike sharing system (BSS) facilitates people's travel, relieves traffic jams, and mitigates carbon emissions. In this research, a basic method is proposed to measure the carbon emission mitigation of dock-less BSS from the perspective of life cycle analysis (LCA). The method is applied in a typical city of China (i.e., the city of Beijing). The carbon emissions of six models of shared bikes in Beijing are calculated in this paper. The results indicate that: (a) the use process of dock-less BSS has mitigated carbon emissions in the central district of Beijing (9.23 Mt CO$_{\text{2-eq}}$ in 2016 and 9.26 Mt CO$_{\text{2-eq}}$ in 2017); (b) in consideration of all life cycle processes of BSS, the carbon emissions actually has risen with the best scenario of 10% substitute rate (i.e., 33.2 Mt CO$_{\text{2-eq}}$ in 2016 and 80.9 Mt CO$_{\text{2-eq}}$ in 2017); (c) the carbon mitigation effect of BSS is closely related to the processes of production, maintenance and rebalancing. Finally, to promote the effect of carbon mitigation, it is necessary to control the number of shared bikes and increase their utilization rate.